The Effect of Emotional Maturity on Student Discipline in Participating in Activities at the College of Qur'an Sciences (STIQ) Amuntai - Assya’bani, Ridhatullah; Huda, Nuril; Hermina, Dina; Imraan, Mohd; Nasir, Muhammad (PDPI (Perkumpulan Dosen Peneliti Indonesia), 2024)
The activities of STIQ Amuntai’s student, which is very different from student life in general, entering a new environment for students become a stimulus that sometimes causes various problems, one of which is self-adjustment, either with themselves, peers or the surrounding environment so. The purpose of this study is to find out the level of emotional maturity and the level of discipline of students along with to determine the influence of maturity on student discipline at STIQ Amuntai. This research method is a quantitative method by taking 44 student samples. This research was conducted using a questionnaire method consisting of 2 scales, namely the emotional maturity scale and the discipline scale. To find out the effect of emotional maturity on discipline, this data analysis technique will eliminate the rebound with the IBM 25 SPSS for Windows program. Based on the results obtained, namely the distribution of the high category there are 4 students representing 9.1% while in the medium category there are 36 students with a percentage of 81.8%, in the low category there are 4 students representing 9.1%. The dominance of the results of the research on emotional maturity in STIQ Amuntai students shows the dominance of the results in moderate categorization. The level of discipline of STIQ Amuntai students is predominantly moderate, the distribution of discipline categorization is as follows: 63.6% is classified as moderate amounting to 28 students, 18.2% is classified as high amounting to 8 students and 18.2% is classified as low amounting to 8 students. Based on the results of the study which shows that STIQ Amuntai is dominated at a moderate level of categorization. It is known that the Pearson correlation coefficient (r) of 0.318 means that the correlation between emotional maturity and discipline in STIQ Amuntai students is 0.318 or classified as a sufficient correlation coefficient because the value of the correlation coefficient is at a value of 0.26 – 0.50 and is in the category of sufficient correlation relationship. In addition, a significance value (p) of 0.035 < 0.05 can be interpreted that there is a positive and significant influence between emotional maturity and discipline. Here it can be interpreted that emotional maturity has a significant influence on the discipline of STIQ Amuntai students